Splenic Artery Infarct Requiring Surgery: A Rare Complication of COVID-19 Infection - Ioannis Dimitriou; Nikolaos Christodoulou; Kleanthis Chatzimargaritis; Aristidis Kaikis; Eirini Kasti; Georgios Triantos (Case Reports in Surgery)
Introduction. Coronavirus disease (COVID-19) from SARS-CoV-2 infection is linked to a hypercoagulable state, leading to arterial and venous thrombotic events, of which pulmonary embolism is the most frequent. However, arterial thromboembolisms may also occur as visceral infracts in unusual sites, such as the renal, splenic, and intestinal arteries. Case Report. A 46-year-old unvaccinated male with a COVID-19 infection was admitted to the COVID-19 isolation ward with symptoms of respiratory infection. He complained of epigastric pain and fever for several days; radiological imaging of the abdomen revealed complete splenic arterial occlusion due to a large infarct. He was treated with low molecular weight heparin (enoxaparin) in therapeutic doses, resulting in minimal improvement. However, the pain worsened, and eventually, a laparotomy and splenectomy were performed. He was hospitalized for another 36 days before he was discharged in good condition. A second surgery was performed to remove a noninfected encapsulated hematoma from the subdiaphragmatic space. The patient remained healthy afterward, with no relapses. Discussion. Although rare, the number of cases of visceral infarcts in COVID-19 patients has increased. Splenic artery infarct is an exceptional case of acute abdominal pain that can be treated successfully with anticoagulant medication. Splenectomy may be required to manage refractory pain after failure of conservative management.